Anatomical observations on the smaller sublingeal nerves - Zorzetto, N. L.; Manubens, R. S.; Pessoa de Andrada, E. (My University, 1985)
The nervous sublingual plexus was studied in 25 cadavers. One to 13 smaller sublingual branches, which spread through the sublingual region formations, were observed. These branches derive from the lingual nerve before and after the sublingual nerve origin. The proximal branches establish wide intercommunications with the sublingual nerve and its branches by means of well-individualized communicating loops in the sublingual plexus set.